2021
DOI: 10.12944/carj.9.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Is Africa Ready for the SDG 2 (Zero Hunger) Target by 2030?

Abstract: In recent time, the prevalence of hunger, malnutrition and food insecurity have increased in most African countries as the continent continued to experience rising number of people that are undernourished. This paper reveals the progress of African region in pursuit of SDG 2 target by 2030 considering both the global and Africa SDG threshold (rating) in 2019. The SDG2 target achievement in Africa is facing serious obstacles such as high level of poverty, unemployment, social exclusion, corruption, banditry, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, previous studies reported less diverse diets, poor healthcare access, unimproved toilet facilities, and epileptic power supply (and near zero access to electricity) as part of the factors influencing the prevalence of malnutrition (poor nutritional status) among young children in Nigeria and most Sub-Saharan African countries (UNICEF, 2021 ; Omotayo et al, 2021 ; Adeyonu et al, 2022a ; Otekunrin & Otekunrin,; Otekunrin et al, 2022a ; Otekunrin, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies reported less diverse diets, poor healthcare access, unimproved toilet facilities, and epileptic power supply (and near zero access to electricity) as part of the factors influencing the prevalence of malnutrition (poor nutritional status) among young children in Nigeria and most Sub-Saharan African countries (UNICEF, 2021 ; Omotayo et al, 2021 ; Adeyonu et al, 2022a ; Otekunrin & Otekunrin,; Otekunrin et al, 2022a ; Otekunrin, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2019, under-five children malnutrition surged with 21.3% (144.0million) stunted, 6.9% (47.0million) wasted and 5.6% (38.3million) overweight. Meanwhile, empirical evidence revealed that 20million babies are born with low birth weight annually while overweight and obesity adults are at critical level of about 40% (Global Nutrition Report, 2018UNICEF et al 2020;Otekunrin & Otekunrin 2021a). Meanwhile, in 2020, the number of under-five children that are stunted climbed to 149.2million, 45.4million are wasted while 38.9million are overweight (Global Nutrition Report, 2021;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy of note that 38.9%, 58.4%, and 39.1% of the rural households in Nigeria had access to electricity, good source of drinking water, and improved toilet facilities respectively (NPC and ICF 2019 ). However, empirical reports also revealed that the proportion of undernourished population in Nigeria moved up from about 10% in 2000 to 14% in 2018 (von Grebmer et al 2019 ; Otekunrin et al 2020a ; Ayinde et al 2020 ; Otekunrin 2021 ). Studies by International Food Policy Research Institute (IFPRI) reported that most of the undernourished population in developing countries are members of smallholder farming households especially in developing low- and middle-income countries who depend mainly on agriculture as significant means of livelihood with almost no social support interventions (IFPRI 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Sen (2000, 2) conceives development to include "being able to avoid such deprivations as starvation, undernourishment, escapable morbidity, and premature death." Otekunrin et al (2021) observe that African countries are bedevilled by a myriad of challenges which have been aggravated by the ravages occasioned by COVID-19. Witon (2015) concluded that there is no significant socio-economic difference between various sub-regions of the continent.…”
Section: Introductionmentioning
confidence: 99%